2015
DOI: 10.1128/jvi.01297-15
|View full text |Cite
|
Sign up to set email alerts
|

DDX60L Is an Interferon-Stimulated Gene Product Restricting Hepatitis C Virus Replication in Cell Culture

Abstract: All major types of interferon (IFN) efficiently inhibit hepatitis C virus (HCV) replication in vitro and in vivo.Remarkably, HCV replication is not sensitive to IFN-␥ in the hepatoma cell line Huh6, despite an intact signaling pathway. We performed transcriptome analyses between Huh6 and Huh-7 cells to identify effector genes of the IFN-␥ response and thereby identified the DExD/H box helicase DEAD box polypeptide 60-like (DDX60L) as a restriction factor of HCV replication. DDX60L and its homolog DEAD box poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 73 publications
(116 reference statements)
1
66
0
1
Order By: Relevance
“…These observations indicate that DDX60 promotes both viral RNA degradation and recognition, similar to ZAPS (Figure C). Knockout studies revealed that mouse DDX60 is required for full RIG‐I activation in mouse embryonic fibroblasts and peritoneal macrophages but not bone marrow‐derived dendritic cells , while DDX60 ‐independent RIG‐I activation in mouse cells has also been reported . These findings indicate that DDX60 ‐mediated RIG‐I activation is cell type‐specific.…”
Section: Links Between Viral Rna Recognition and Degradationmentioning
confidence: 94%
“…These observations indicate that DDX60 promotes both viral RNA degradation and recognition, similar to ZAPS (Figure C). Knockout studies revealed that mouse DDX60 is required for full RIG‐I activation in mouse embryonic fibroblasts and peritoneal macrophages but not bone marrow‐derived dendritic cells , while DDX60 ‐independent RIG‐I activation in mouse cells has also been reported . These findings indicate that DDX60 ‐mediated RIG‐I activation is cell type‐specific.…”
Section: Links Between Viral Rna Recognition and Degradationmentioning
confidence: 94%
“…DDX60L neighbors DDX60 on chromosome IV, and its amino acid sequence is B70% homologous to DDX60 [71]. However, our knowledge on functions of DDX60L in innate immunity is still scarce.…”
Section: Ddx60lmentioning
confidence: 99%
“…However, our knowledge on functions of DDX60L in innate immunity is still scarce. A study from 2015 describes DDX60L as an innate immune effector of type I, type II, and type III IFN response that acts independently of DDX60 against hepatitis C virus (HCV) in liver cells [71]. The expression of DDX60L is induced soon after the acute HCV infection, during which it represses the viral RNA replication in a manner independent of IRES-mediated translation or RNA stability, and enhances RIG-I-dependent IRF3 activation [71].…”
Section: Ddx60lmentioning
confidence: 99%
See 2 more Smart Citations